Comparing team performance of the English Premier League, Serie A, and La Liga for the 2008-2009 season - Oberstone, J. (Journal of Quantitative Analysis in Sports, 2011)
Three of the most celebrated football leagues in the world include the English Premier League (EPL), Italy`s Serie A, and Spain`s La Liga. To date, little football research has been conducted that attempts to determine why these leagues are so successful. What is it that the EPL, La Liga, and Serie A do that fosters such a high caliber of play, and what pitch factors, if any, either (1) contrast or (2) connect these prestigious leagues? The paucity of rigorous inquiry has not deterred popular speculation—common folklore has not waited for hard data. Experts rush to characterize the perceived performance characteristics of these leagues with little hesitation. And these assumptions have, to some degree, taken on a life of their own: football`s answer to urban legend.